2000
DOI: 10.4049/jimmunol.164.9.4635
|View full text |Cite
|
Sign up to set email alerts
|

Increased DNA Vaccine Delivery and Immunogenicity by Electroporation In Vivo

Abstract: DNA vaccines have been demonstrated to be potent in small animals but are less effective in primates. One limiting factor may be inefficient uptake of DNA by cells in situ. In this study, we evaluated whether cellular uptake of DNA was a significant barrier to efficient transfection in vivo and subsequent induction of immune responses. For this purpose, we used the technique of electroporation to facilitate DNA delivery in vivo. This technology was shown to substantially increase delivery of DNA to cells, resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
306
2
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 550 publications
(328 citation statements)
references
References 27 publications
(30 reference statements)
12
306
2
3
Order By: Relevance
“…The pulse parameters, ie electric field and duration, were consistent with those in previous investigations on cell transfection via electroporation in vivo. [9][10][11] The vector of total DNA movement per pulse was determined by maximizing the normalized correlation coefficient of two fluorescence images of DNA taken between successive pulses. A vector representing tissue deformation or movement, due to electrolysis at the tissue-electrode interfaces, was determined by tracking bead coordinates in fluorescence images taken between successive pulses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pulse parameters, ie electric field and duration, were consistent with those in previous investigations on cell transfection via electroporation in vivo. [9][10][11] The vector of total DNA movement per pulse was determined by maximizing the normalized correlation coefficient of two fluorescence images of DNA taken between successive pulses. A vector representing tissue deformation or movement, due to electrolysis at the tissue-electrode interfaces, was determined by tracking bead coordinates in fluorescence images taken between successive pulses.…”
Section: Resultsmentioning
confidence: 99%
“…5,9,24,25 Although higher strength pulses (eg 500-3000 V/cm), with durations in the microsecond range, have been demonstrated to be useful in transfecting cells in vitro, [26][27][28] Lucas et al 29 demonstrated that low voltage, millisecond duration pulses resulted in a higher gene expression in vivo than high voltage, microsecond duration pulses. A reduction in pulse duration from a millisecond to a microsecond range may cause DNA electrophoresis to be ineffective, as found in our in vitro experiments using 2% agarose gels (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The plasmid DNA was routinely electroinjected into mouse skeletal muscle in view of the enhanced transduction and immunogenicity connected with this particular procedure. 11,12 The cellular immunity elicited by the different immunization regimens was measured by Elispot assay 2 weeks after the boost. To compare the immunogenic efficiency of the different vaccination regimens, a pool of 15 mer peptides overlapping by 11 aa and covering aa 497-703 (pool D) were used to stimulate antigen-specific IFNc secretion from splenocytes.…”
Section: Construction Of Human Cea Expression Vectorsmentioning
confidence: 99%
“…In vivo electroporation (EP) of plasmid DNA has resulted in increased DNA uptake, leading to enhanced protein expression in treated muscle 9 and in a concomitant increase in the immune responses to the target antigen in a variety of species. [10][11][12][13] This enhancement of immunogenicity mediated by EP could, however, also derive from undefined adjuvant effects connected with transfection of other cells, muscle damage and/or release of danger signals. [14][15][16] Viruses have highly evolved structures that enable them to bind cells and deliver genes into the cells they infect.…”
mentioning
confidence: 99%
“…1 Some applications of ET now envisioned are the endogenous synthesis of EPO, 2 of the soluble receptor to TNFa 3 and of the antiinflammatory cytokine IL-10, 4,5 as well as tumour gene therapy, 6,7 restoration of muscle structural proteins, 8 and DNA vaccination. 9 ET is also applied to tumour electrochemotherapy, 10 where protocols with high voltage and short duration pulses allow antitumoral drugs to be locally delivered to tumour cells. Various ET protocols have been tested on mice skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%